The Influence of Entrepreneurial Orientation and Skills on the Performance of SMEs in the Food and Beverage Sector - Amrullah, Wahyu; Mulyana, Asep; Sutisna, Sutisna (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This research examines the influence of entrepreneurial orientation and entrepreneurial skills on the performance of SMEs in the food and beverage sector in Batu, East Java. The population in this study is food and beverage SMEs owners in the town of Batu, and the samples taken in this study are 50 respondents using non-probability sampling techniques with a purposive sampling method based on predetermined criteria. The first criterion is having more than five employees; the second criterion is the length of time the business has been running for over two years. This type of research is quantitative research with descriptive and verification analysis. The data used in this research is primary data from questionnaires distributed and secondary data from websites, BPS, and journals. Data analysis in this study used descriptive analysis and Partial Least Square Structural Equation Modeling (PLS-SEM) version 3.0 and SPSS version 22. This research found that the first and second hypotheses were accepted, where the entrepreneurial orientation variable had a positive and significant effect on SMEs performance, and entrepreneurial skills had a positive and significant impact on SMEs performance. The findings of this research can become a reference for business actors, academics, and the government in their relations regarding the performance of SMEs.